2010
DOI: 10.2298/mpns1008465p
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diet with reduction in calorie intake on metabolic syndrome parameters in obese subjects with impaired glucose tolerance

Abstract: These results suggest that implementation of low calorie-high fibers diet with balanced nutritive elements have a positive effect on visceral obesity, fasting glucose, lipid profile, and hypertension in obese people with impaired glucose tolerance and lead to consecutive lowering of cardiometabolic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Six studies [ 62 , 67 , 71 , 99 , 102 , 109 ] reported low calorie interventions in people with prediabetes, achieved either through restrictions on all food classes or manipulation of a specific food group. Four studies reported low-calorie dietary interventions that were achieved through restrictions on the daily intake of all food classes, with intervention durations lasting from eight weeks to 12 months [ 62 , 67 , 102 , 109 ]. Daily energy allowances ranged from 415–1700 kcal, distributed with macronutrient compositions of 41–65% carbohydrates, 12–43.7% protein and 13–30% fat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies [ 62 , 67 , 71 , 99 , 102 , 109 ] reported low calorie interventions in people with prediabetes, achieved either through restrictions on all food classes or manipulation of a specific food group. Four studies reported low-calorie dietary interventions that were achieved through restrictions on the daily intake of all food classes, with intervention durations lasting from eight weeks to 12 months [ 62 , 67 , 102 , 109 ]. Daily energy allowances ranged from 415–1700 kcal, distributed with macronutrient compositions of 41–65% carbohydrates, 12–43.7% protein and 13–30% fat.…”
Section: Resultsmentioning
confidence: 99%
“…Daily energy allowances ranged from 415–1700 kcal, distributed with macronutrient compositions of 41–65% carbohydrates, 12–43.7% protein and 13–30% fat. The studies reported reductions in fasting blood glucose levels, which corresponded to a decrease in insulin resistance in three of the studies [ 62 , 102 , 109 ]. Measures of anthropometry changed considerably after intervention, with decreases in body weight [ 67 , 102 , 109 ] and waist circumference [ 62 , 67 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance is associated with impaired lipid oxidation in mitochondria, accumulation of lipid metabolites and inactivation of the insulin signal. Moderate weight loss in obese patients reduces the risk of diabetes by about 50%, with a favorable effect on the lipid status 8,9 . Results of recently published Look AHEAD study 10 demonstrated significant improvement in glucose control in the group of obese patients with T2DM with lifestyle changes that included diet therapy and physical activity.…”
Section: Diabetes Remission After Bariatric Surgerymentioning
confidence: 99%
“…Increased caloric intake is directly related to the development of insulin resistance [11]. This imbalance in energy consumption leads to obesity, and in 1988, Reaven [12] was among the first to associate the hypertrophy of adipose tissue, commonly found in obese patients, with IR.…”
Section: Introductionmentioning
confidence: 99%